Uppsamlings- och behandlingsvagn för smågrisar i samband med kastration - Ullertun, Emma Lucia (SLU/Dept. of People and Society, 2010)
The study investigates the use of collection and treatment wagon for piglets in relation to castration. The importance of good and ergonomically designed tools in pig stables can probably reduce the risk of suffering from musculoskeletal disorders (MSD). During the last 20 years the number of pig farms has decreased and at the same time the herd sizes and the number of pig keepers have increased (Statistic Sweden (SCB) 2007). As a consequence, the pig keepers have more pigs to take care of, treat and neuter and spend more of their daily work in these large confinements. This also means that the repetitive work e.g. treatment, grinding of teeth and castration of piglets increases. These work tasks are difficult to avoid because they are an important part of the pig farming.